Live Human Detection for Robotics in Urban Search and Rescue - Basu, Sadeb; Bose, Rajdip; Mondal, Tushar; Dutta, Sourav; Bhunia, Arpan; Chakraborty, Debraj (International Journal of Computer Sciences and Engineering, 2025)
In this modern world of globalization, high speed technology and automation we can make robots which are faster, more efficient as well as intelligent according to our own work requirements with the help of proper knowledge on advance robotics and with the use of proper equipments. Each and every year in various parts of the world, due to natural calamity (e.g. earthquakes, landslides etc) or by any other sudden disaster which happens without any warning (e.g. sudden collapse of manmade structures such as bridges and high rise buildings, etc), many humans gets stuck and remains buried underneath various materials. It becomes impossible to detect them through conventional search and rescue operations (e.g. sniffer dogs) among the debris and are not rescued. These humans die eventually from suffocation or infection occurring in heavily injured body parts. But with the use of “Live Human Detection for Robotics in Urban Search and Rescue” we can still save maximum of them within a very short interval of time.